Experience in the Development of a Functional Inventory of Imaging Medical Equipment - Martínez-Chávez, G. A. (Revista Mexicana de Ingenieria Biomedica, 2017)
Healthcare institutions in Mexico have gained experience in the administration of their processes. The key to success lies in the management of existing resources, as long as these are adequate, their effectiveness will be greater. This document is aims to provide a procedure that supports the planning and decision-making functions of imaging equipments, under the criterion of having a functional inventory of X Ray equipment in medical care units of South Delegation of the Mexican Institute of Social Security (IMSS) of Mexico City. In this report it is described the type of equipment used in radiology and other imaging services. Its geographical distribution, average functional age and its productivity are analyzed. The Inventory reported 198 pieces of radiology equipment, equipments of 300 mA or 500 mA the most common type (43.94%) followed by ultrasound (29.80%) and fluoroscopy units (21.21%). Follow-up in the inventory should help in planning the acquisition and maintenance of medical equipment within the Delegation.